2007
DOI: 10.1107/s002188980700461x
|View full text |Cite
|
Sign up to set email alerts
|

Melting behavior of polymorphic crystals of poly(trimethylene 2,6-naphthalate) studied by simultaneous synchrotron X-ray scattering and thermal analysis

Abstract: The polymorphic crystallization and melting behavior of poly(trimethylene 2,6‐naphthalate) (PTN) have been investigated using small‐angle X‐ray scattering and simultaneous wide‐angle X‐ray scattering (WAXS) and differential scanning calorimetry (DSC). The α‐crystal, the β‐crystal and the coexistence of both crystal forms of PTN develop at an isothermal temperature below 393 K, above 453 K and between these two temperatures, respectively. The simultaneous WAXS/DSC measurement provides a good way to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The structure changes of PTN α-form observed by WAXS are consistent with that observed by DSC. Chuang et al observed some diffraction peaks of β-form crystal when the α-form crystal was heated at temperature above 170 °C. They explained that the part of α-form crystal may be transformed into the β-form crystal during the heating process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structure changes of PTN α-form observed by WAXS are consistent with that observed by DSC. Chuang et al observed some diffraction peaks of β-form crystal when the α-form crystal was heated at temperature above 170 °C. They explained that the part of α-form crystal may be transformed into the β-form crystal during the heating process.…”
Section: Resultsmentioning
confidence: 99%
“…They explained that the part of α-form crystal may be transformed into the β-form crystal during the heating process. Chuang et al noticed that the WAXS profile measured during the α-form to β-form crystal transformation is different from that of the coexistence of α- and β-crystals. In our work, however, we did not observe PTN β-crystal diffraction peaks when the PTN α-form crystal was heated or annealed at above 170 °C of temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations